PENERAPAN INKUIRI TERSTRUKTUR TERHADAP PENINGKATAN KETERAMPILAN PROSES SAINS PESERTA DIDIK PADA MATERI GERAK - Anindya Dhara Amarna; Wahono Widodo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze students' science process skills on motion material. The results of the pre-research indicate that students' KPS on each indicator is in the low category. In improving science process skills, it is necessary to be supported by an appropriate learning model, one of which is the structured inquiry model. The structured inquiry learning model can invite students to be active during the learning process. This type of research is applied with a pre-experimental method and applies a one-group pre-test and post-test design. The study was conducted in one of Surabaya's Public Junior High Schools with a sample of 31 students in class VII-G. Data on science process skills on motion material were obtained using pre-test and post-test question instruments. The results of the study that have been conducted show that students' science process skills experienced a significant increase after the implementation of the structured inquiry learning model, which is indicated by the average value of the pre-test post-test N-gain of 0.66 with a moderate category. Each indicator of science process skills also experienced an increase that can be seen from the average N-gain of all indicators of 0.67 with a moderate category. Therefore, the application of a structured inquiry learning model to motion material is effective in improving the science process skills of junior high school students.